Perception of sexual harassment among public administrators - Marican, Sabitha (2000)
The problem of sexual harassment exist in most cultures, and in many different settings,be it in public places, educational institutions or at the work place.This problem is also greater for women than men.Past studies and statistics in Malaysia indicated that as this problem do not exist here.How ever the silence occurance of sexual harassment prompted NGO's like WCC, Awam together with public agencies to advocate specific laws to combat this phenomenon.Thus in lieu of this situation the objective of this is to identify the bahaviors that are perceived as sexually harassing in accordance with local and in difineous definition, amongst public administrators in the northern region of Malaysia.The main instrument of the study was adapted based on several previous questionaire and aptly termed as Utara Sexual Harassment Perseption Questionnaire (USHPQ).A total of 1100 questionnnaire were sent to 60 public sector departments in 4 state and 586 were returned and used tor analysis.Four types of sexual harassment were identified; visual, physical, non-verbal and verbal.Respondents perceived visual quest as most harassing, followed by physical, non-verbal and verbal.A total of 83.1% sees it as more harassing when done by men onto women.Majority agreed that their organization do not have any procedures to manage SH complaints, felt that it is important to have anti SH act in the organization, but also felt confident that reports of SH will be acted upon by organization when lodged by the harassed person.However various views were provided to what will happen to employees who lodged SH reports.Findings were discussed in accordance to previous findings and some to employees who lodged SH reports.Findings were discussed in accordance to previous findings and some popular SH theoretical constructs.